One-step functionalization of magnetic nanoparticles with 4-mercaptophenylboronic acid for a highly efficient analysis of N-glycopeptides. Issue 41 (13th October 2017) - Yao, Jizong; Wang, Jiawen; Sun, Nianrong; Deng, Chunhui
Abstract : A very simple and amazing approach was proposed to synthesize MPBA functionalized magnetic nanoparticles via the interaction between Fe and SH, and the as-prepared nanoparticles were successfully applied for the efficient analysis of glycopeptides in complex bio-samples with sensitivity and selectivity. Abstract : A very simple and amazing approach was proposed to synthesize MPBA functionalized magnetic nanoparticles via the interaction between Fe and SH, and the as-prepared nanoparticles were successfully applied for the efficient analysis of glycopeptides in complex bio-samples with sensitivity and selectivity.